A Turkish woman's European impressions - Zeynep Hanım, 1884-1923. (Piscataway, NJ)
xxvii, 246 sayfa, [16] sayfa resim, çizim, portre
Keywords: “Born into the Ottoman Muslim elite, Zeyneb Hanoum and her sister Melek Hanoum were given a Western-style education by their progressive father, who expected them subsequently to live the segregated lives of Ottoman ladies. Rebelling, the sisters collaborated with the French author Pierre Loti, hoping that harnessing European intellectual support would speed up Ottoman social reform. Fleeing Istanbul in 1906 for fear of imperial reprisals, the sisters traveled in disguise to Europe, hoping to find “freedom“ in the West. With Zeyneb Hanum's letters punctuated by Grace Ellison's introduction, commentary, and footnotes, this book challenges Orientalist stereotypes and documents the vibrant engagement between Eastern and Western women at the fin de siècle“ -- Yayıncı.